Antibiotic resistance pattern of Pseudomonas aeruginosa isolated from pus samples at tertiary care cancer hospital - Surve, Kapil V.; Khaparkhuntikar, Mukta N.; Siddiqui, Nazneen S.; Iravane, Jyoti A. (International Journal of Research in Medical Sciences, 2024)
Background: Pseudomonas aeruginosa is one of the most frequent opportunistic microorganisms causing infections in cancer patients. The aim of the study was to determine the antibiotic susceptibility of Pseudomonas aeruginosa and multidrug-resistant (MDR) isolates in cancer patients. Methods: A retrospective study was conducted from January 2022 to December 2022 at Government Cancer Hospital, Aurangabad. A total of 143 pus samples were collected from both IPD and OPD patients. Pus samples were collected as per standard procedure and were inoculated on blood and MacConkey agar. The isolates were identified by standard protocols using biochemical tests. The antibiotic susceptibility pattern of each isolate was checked as per Clinical and Laboratory Standards Institute (CLSI) guidelines 2022 using Kirby-Bauer’s disc diffusion method and VITEK 2 Automation. Data analysis was done by statical method with statistical software SPSS version 22. Results: Out of 143 clinical samples 33 samples (23%) were positive for Pseudomonas aeruginosa growth. mean age of patients was 50 years old out of 33 isolates 12 (36%) isolates were multidrug-resistant, 11 (33%) isolates were extensively drug-resistant and 1 (3%) were pan-drug-resistant. The majority of isolates were responsive to polymyxin B 32 (96%) and colistin 32 (96%); However, the resistance to gentamycin, ceftazidime, and amikacin was higher, at 66%, 60%, and 57%, respectively. Conclusions: This hospital-based retrospective study will help to implement better infection control strategies and improve the knowledge of antibiotic resistance patterns among clinicians. Thus, there is a need for an antibiotic stewardship program to monitor the resistant pattern in a tertiary care cancer hospital.